Real-world outcomes of first-line pembrolizumab plus pemetrexed-carboplatin for metastatic nonsquamous NSCLC at US oncology practices - Vamsidhar Velcheti (Nature Portfolio, 2021)
Abstract Evidence from real-world clinical settings is lacking with regard to first-line immunotherapy plus chemotherapy for the treatment of non-small cell lung cancer (NSCLC). Our aim was to describe outcomes for patients treated with first-line pembrolizumab-combination therapy for metastatic nonsquamous NSCLC in US oncology practices. Using an anonymized, nationwide electronic health record-derived database, we identified patients who initiated pembrolizumab plus pemetrexed-carboplatin in the first-line setting (May 2017 to August 2018) after diagnosis of metastatic nonsquamous NSCLC that tested negative for EGFR and ALK genomic aberrations. Eligible patients had ECOG performance status of 0–1. An enhanced manual chart review was used to collect outcome information. Time-to-event analyses were performed using the Kaplan–Meier method. Of 283 eligible patients, 168 (59%) were male; median age was 66 years (range 33–84); and the proportions of patients with PD-L1 tumor proportion score (TPS) of ≥ 50%, 1–49%, < 1%, and unknown were 28%, 27%, 28%, and 17%, respectively. At data cutoff on August 31, 2019, median patient follow-up was 20.3 months (range 12–28 months), and median real-world times on treatment (rwToT) with pembrolizumab and pemetrexed were 5.6 (95% CI 4.5–6.4) and 2.8 months (95% CI 2.2–3.5), respectively. Median overall survival (OS) was 16.5 months (95% CI 13.2–20.6); estimated 12-month survival was 59.5% (95% CI 53.3–65.0); rwProgression-free survival was 6.4 months (95% CI 5.4–7.8); and rwTumor response rate (complete or partial response) was 56.5% (95% CI 50.5–62.4). Median OS was 20.6, 16.3, 13.2, and 13.7 months for patient cohorts with PD-L1 TPS ≥ 50%, 1–49%, < 1%, and unknown, respectively. These findings demonstrate the effectiveness of pembrolizumab plus pemetrexed-carboplatin by describing clinical outcomes among patients with metastatic nonsquamous NSCLC who were treated at US oncology practices.